THE AUTONOMY OF INDONESIAN MUSLIM WOMEN IN THE NOVEL ‘ADHRĀ’ JĀKARTĀ BY NAJĪB AL-KYLĀNĪ: A Feminist Literary Criticism Perspective (State Islamic University (UIN) of Sunan Ampel Surabaya, 2021)
This article reviews the novel ‘Adhrā’ Jākartā (Jakartanese Girl) by Najīb al-Kylānī. Through the approach of feminist literary criticism and the hermeneutic `method it’s aimed to express the autonomy of Indonesian Islamic women within the novel by interpreting the structure of symbols or texts in a number of language signs in the literary system. The results of the analysis revealed that the character of Fāṭimah is a symbol which represents the concept of autonomy of Indonesian Islamic women in the public and domestic sphere due to the universal and cosmopolitan Islamic values that Fāṭimah implements in personal, social, national, and civil life. This universal and cosmopolitan Islam illustrates an Islamic paradigm offered by the author to be translated into a unity in diversity of Indonesian context, so as to be able to present the figure of an autonomous Indonesian Muslim woman in a pluralistic and elastic Indonesian context.